2021
DOI: 10.1093/gerona/glab014
|View full text |Cite
|
Sign up to set email alerts
|

The Great Pond Snail (Lymnaea stagnalis) as a Model of Aging and Age-Related Memory Impairment: An Overview

Abstract: With the increase of life span, normal ageing and age-related memory decline are affecting an increasing number of people; however, many aspects of these processes are still not fully understood. Although vertebrate models have provided considerable insights into the molecular and electrophysiological changes associated with brain ageing, invertebrates, including the widely recognised molluscan model organism, the great pond snail (Lymnaea stagnalis) have proven to be extremely useful for studying mechanisms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 93 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Using our model system, the pond snail Lymnaea stagnalis , we have been able to begin to uncover aspects of the causal neuronal mechanisms underlying learning and its subsequent consolidation into long-term memory (LTM) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using our model system, the pond snail Lymnaea stagnalis , we have been able to begin to uncover aspects of the causal neuronal mechanisms underlying learning and its subsequent consolidation into long-term memory (LTM) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we found that amyloid-β peptides 1-42 and 25-35 were able to inhibit longterm memory recall in L. stagnalis (Ford et al, 2017;Ford et al, 2015). Recently, the sequencing of the whole transcriptome of the central nervous system (CNS) of L. stagnalis identified several evolutionarily conserved sequences of genes involved in human ageing, and age-related and amyloid-β-induced memory loss, including gelsolin, presenilin, huntingin, Parkinson disease protein 7 (PARK-7/DJ-1) and amyloid precursor protein (Fodor et al, 2021;Fodor et al, 2020b). However, the lack of comprehensive proteomics information in L. stagnalis has hindered further progress with research aimed at understanding the roles of these proteins in the context of large-scale protein networks in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Lymnaea stagnalis , also known as the great pond snail, is an excellent model organism used for research in neuroscience, aging, ecotoxicology, parasite-host interactions, and evolution and development ( Jimenez et al, 2004 ; Hoek et al, 2005 ; Benjamin, 2008 ; Pirger et al, 2014 ; Fodor et al, 2020a , b , 2021 ). Specifically, the central nervous system (CNS) of L. stagnalis is highly characterized at multiple levels.…”
Section: Introductionmentioning
confidence: 99%